KEMAMPUAN BERPIKIR KRITIS SISWA MENGGUNAKAN INSTRUMEN SOAL BERBASIS KEARIFAN LOKAL KUE KLEPON PADA MATERI KALOR - Mardatillah, Mabita; Sutarja, Maria Chandra; Ahied, Mochammad; Hadi, Wiwin Puspita; Yamin, Yamin (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2025)
The purpose of this study was to identify students critical thinking skills using a question instrument based on local wisdom of klepon cake on heat material. This research uses quantitative descriptive research. The study population was all students of SMPN Kraton kabupaten Pasuruan. Sampling using purposive sampling technique non probability sampling type. The sample used ini this study was class VII SMPN Kraton kabupaten Pasuruan. Data were collected using test and documentation. The result showed that studentes critica; thinking skills were still relatively low with an average of 50.59% of the percentage of the number of students in class VII SMPN Kraton kabupaten Pasuruan. The value of critical thinking skills in each aspect of the critical thinking skill indicator explains that the focus aspect is 23.38, the reason aspect is 20.63, the inference aspect is 37.57, the situation aspect is 19.84, the clarity aspect is 24.87 and the overviewe aspect is 33.60